Penerapan Metode Index Card Match untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar pada Mata Pelajaran Asmaulhusna - Jefri Murdani Putra (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Islamic religious education is an effort and care for students so that later after completing education can understand what is contained in Islam as a whole, appreciate the meaning and purpose, and ultimately practice it and make the teachings of Islam that he has embraced as his view of life so that it can bring salvation in the world and the hereafter. The purpose of this study was to determine how much influence the application of the index card match method has on improving student learning outcomes in Islamic Religious Education subjects on asmaulhusna material at SDN 14 Penarik 2023-2024. The research design used the Classroom Action Research (PTK) model Kemmis and Mc Taggart. This research was conducted at SD Negeri 14 Penarik, Mukomuko Regency in 2023. Data collection using observation, tests, and interviews. Data analysis using the value of learning completeness. The results showed that the application of the index card match method can improve student learning outcomes in asmaulhusna lessons. The existence of this increase can be seen from the learning outcomes of students in each cycle.